Linear and nonlinear finite strip analysis of bridges. - Li, Wenchang. (University of Ottawa (Canada), 1991)
The analysis of highway bridges such as slab-on-girder bridges, box-girder bridges, cable-stayed bridges etc. is a very complicated undertaking. Analytical methods are applicable only for the simplest structures. Finite element method is the most powerful and versatile tool, which can be applied to analyze any types of bridge and any load cases. However, the efficiency of that method needs to be improved because the finite element solutions usually require too much computer time, too large core storage and too many input data. If a structure has a uniform cross-section and line end supports (in fact, a high proportion of bridges can be simplified to such a structure), the finite strip method has proven to be the most efficient numerical structural analysis method, which employs a series of functions to simulate the variation of displacements in the longitudinal direction of the structure. Thus, the number of dimensions of analysis is reduced by at least one. Consequently, the computer time, storage and input data are reduced significantly. Since this method was first published in 1968, it has been extensively used for linear and nonlinear, static and dynamic analysis of rectangular, skew and curved slab bridges, slab-on girder bridges box-girder bridges etc. In the present study, the following efforts are made: (1) Extending the finite strip method to the analysis of continuous haunched slab-on-girder bridges and box-girder bridges. (2) Extending the spline finite strip method to the analysis of continuous haunched slab-on-girder bridges and box-girder bridges. (3) Extending the finite strip method to nonlinear analysis of cable-stayed bridges. (4) Improving the efficiency of geometrically nonlinear finite strip analysis of plates. (5) Improving the accuracy of materially nonlinear finite strip analysis of reinforced concrete slabs. (6) Combining the finite strip method with finite element method and boundary element method for analysis of rectangular plates with some irregularities. A number of numerical examples will show the accuracy and efficiency of the methods developed in the present study.
Keywords: Engineering, Civil.